2009
DOI: 10.1115/1.4000257
|View full text |Cite
|
Sign up to set email alerts
|

CFD Modeling and X-Ray Imaging of Biomass in a Fluidized Bed

Abstract: Computational modeling of fluidized beds can be used to predict the operation of biomass gasifiers after extensive validation with experimental data. The present work focused on validating computational simulations of a fluidized bed using a multifluid Eulerian-Eulerian model to represent the gas and solid phases as interpenetrating continua. Simulations of a cold-flow glass bead fluidized bed, using two different drag models, were compared with experimental results for model validation. The validated numerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…The literature on this topic is abundant; from the earlier works of Boemer et al (1998), and Van Wachem et al (1998), to the more recent studies comprising image analysis (Busciglio et al, 2009), particle drag optimisation procedures (Mahinpey et al, 2007;Vejahati et al, 2009), and time averaged volume fraction (Deza et al, 2009;Min et al, 2010;. Particularly, the works of Deza et al (2009) and Min et al (2010) show a reasonable agreement between two dimensional (2D) and three dimensional (3D) simulations and X ray imaging experiments of cylindrical fluidized beds of internal diameter of 0.095 and 0.152 m, respectively. compared their 3D simulation results of time average solids volume fraction in a bubbling bed with experimental data from g ray absorption, capa citance probe and differential pressure measurements, and showed that industrial scale fluidized beds can be reasonable predicted with acceptable computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on this topic is abundant; from the earlier works of Boemer et al (1998), and Van Wachem et al (1998), to the more recent studies comprising image analysis (Busciglio et al, 2009), particle drag optimisation procedures (Mahinpey et al, 2007;Vejahati et al, 2009), and time averaged volume fraction (Deza et al, 2009;Min et al, 2010;. Particularly, the works of Deza et al (2009) and Min et al (2010) show a reasonable agreement between two dimensional (2D) and three dimensional (3D) simulations and X ray imaging experiments of cylindrical fluidized beds of internal diameter of 0.095 and 0.152 m, respectively. compared their 3D simulation results of time average solids volume fraction in a bubbling bed with experimental data from g ray absorption, capa citance probe and differential pressure measurements, and showed that industrial scale fluidized beds can be reasonable predicted with acceptable computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…The use of CFD to model fluidized beds is highly dependent on the boundary conditions and validation through experimentation. Deza et al [8,9] and Min et al [10] have shown that X-ray visualization techniques can be used as a validation tool for fluidized bed hydrodynamic simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The grid resolution study by Deza et al [30] identified a sufficient number of cells that would produce an estimated numerical error less than 1%. The study was for a 2D domain, where a total of 2400 grid cells provided adequate resolution of the domain.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the ground walnut shell particle properties and flow conditions. To account for the non-spherical nature of the ground walnut shell (it is more chunk-like), the sphericity and coefficient of restitution were numerically estimated based on previous work by Deza et al [30], whereas the other properties were provided from the experiments. Two inlet gas velocities are examined; the lower velocity of U g ¼ 1:5U mf represents a mild bubbling bed and the higher velocity of U g ¼ 3:0U mf represents a moderate industrial reactor flow rate [34], where U mf is the minimum fluidization velocity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation